Development of a Bioprocess for the Production of Cyclic Lipopeptides Pseudofactins With Efficient Purification From Collected Foam - Biniarz, Piotr; Henkel, Marius; Hausmann, Rudolf; Łukaszewicz, Marcin (Frontiers in Bioengineering and Biotechnology, 2020)
Microbial surfactants (biosurfactants) have gained interest as promising substitutes of synthetic surface-active compounds. However, their production and purification are still challenging, with significant room for efficiency and costs optimization. In this work, we introduce a method for the enhanced production and purification of cyclic lipopeptides pseudofactins (PFs) from Pseudomonas fluorescens BD5. The method is directly applicable in a technical scale with upscaling possible. It combines increased yield of ~7.2 grams of PFs per 30 L working volume, with high recovery levels (80-90%) and initial purity of raw PFs (60-70%), achieved with an innovative single-step thermal co-precipitation and extraction directly from collected foam. We also present a protocol for the selective production of PF structural analogues and their separation with HPLC. Our approach can be potentially utilized in the efficient production of other lipopeptides of Pseudomonas and Bacillus origin.